Utilization of Chatbot AI to Improve the Accessibility and Effectiveness of Guidance and Counseling Services in the Digital Era: A Literature Review - Hesti, Ikma; Yunizahrani, Auliya; Saskia, Cintia; Tohamba, Citra Prasiska Puspita; Nurhikma, Nurhikma (JUPE : Jurnal Pendidikan Mandala, 2025)
Guidance and counseling (GC) services across educational, public health, and industrial contexts face core challenges: limited professional workforce, geographical barriers, and stigma that impede user access. This systematic literature review analyzes the potential of AI chatbots as a supportive solution for GC services in the digital era. Data were collected from 32 scientific journals (2018–2025) and practical reports, then analyzed using a thematic approach. The findings reveal that AI chatbots improve service accessibility through three key avenues: (1) 24/7 availability without location restrictions, (2) up to 40% reduction in operational costs for service providers, and (3) stigma mitigation via anonymous interactions. Additionally, chatbots equipped with natural language processing (NLP) algorithms and psychological data training enhance service effectiveness by delivering initial mental health symptom screening (78% accuracy based on a case study in Indonesian secondary schools), simple coping guidance, and referrals to professionals when necessary. However, the study identifies critical challenges: the risk of misinterpreting emotional context, limitations in addressing complex cases (such as severe depression), and user data privacy concerns. Based on these results, the study recommends a collaborative model between AI chatbots and GC professionals, as well as the implementation of strict data regulations to ensure service safety and relevance. This review concludes that AI chatbots are valuable supportive tools for expanding the reach of GC services but cannot replace the human role in addressing complex emotional needs.